Zero party data between hype and hope - Polonioli, Andrea (Frontiers in Big Data, 2022)
Zero Party Data (ZPD) is a hot topic in the context of privacy-aware personalization, as the exponential growth of consumer data collected by retailers has made safeguarding data privacy a key priority. Articles arguing for the value of ZPD to improve personalization and engender consumer trust have appeared in the popular press, in business magazines as well as in academic journals. Advocates of ZDP argue that instead of inferring what customers want, retailers can simply ask them. Provided that the value exchange is clear, customers will willingly share data such as purchase intentions and preferences to improve personalization and help retailers create a picture of who they are. While the rise of ZPD is a welcome development, this paper takes issue with the claim that ZPD is necessarily accurate as it comes directly from the customer. This view is at odds with established conclusions from decades of research in the social and cognitive sciences, showing that self reports can be influenced by the instrument and that people have limited insight into the factors underlying their behavior. This paper argues that while ZDP disclosures are an important tool for retailers, it is critical to carefully understand their limitations as well. The paper also provides a catalog of biases for identifying potential problems in survey design to help practitioners collect more accurate data.